cERBB-2/Her-2 Neu Overexpression and Prognostic Significance in Uterine Carcinosarcoma - Huseyin Salih SEMIZ; Emel Ebru PALA; Behzat CAN; Elif ATAG; Hatice GUNGOR; Muzaffer SANCI (Federation of Turkish Pathology Societies, 2023)
Objective: There is not enough data in the literature regarding Her-2 overexpression in uterine carcinosarcomas or its association with the prognosis. The aim of this study was to determine the Her-2 overexpression rate in uterine carcinosarcoma and to evaluate its relationship with the prognosis. Material and Method: Her-2 protein and gene status were evaluated by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), respectively, in hysterectomy specimens from 51 patients with uterine carcinosarcoma. Results: Her-2 protein expression in the epithelial component was negative in 42 patients (score 0 in 33 cases, score (+1) in 9 cases), score (+2) in 7 patients and score (+3) in 2 patients. None of the patients had Her-2 protein expression within the sarcomatous component of the tumors. Her-2 gene was not amplified in epithelial or mesenchymal tumor areas according to the FISH method. There was no difference between the Her-2 overexpression negative and positive groups in terms of disease-free survival (DFS) and overall survival (OS). Her-2 overexpression was significantly higher in tumors of patients diagnosed at 65 years or older (p=0.046). Conclusion: In our study, no relationship could be shown between Her-2 overexpression and prognosis in uterine carcinosarcoma. More comprehensive studies are needed to illustrate the relationship between Her-2 overexpression and carcinosarcoma prognosis.